Insufficient physical activity level among Sahrawi adults living in a protracted refugee setting - Eivind Andersen; Ida Kjellså; Victoria Telle Hjellset; Sigrun Henjum (BMC, 2021)
Abstract Background The Sahrawi people fled their homes in 1975 as the conflict in Western Sahara escalated and settled down near Tindouf, Algeria, where they still live. High prevalence of overweight and obesity and type 2 diabetes had been found in this protracted refugee setting. Scaling up national policy efforts to promote physical activity (PA) is critical to reducing the prevalence of noncommunicable diseases (NCDs) in the near future. One possible barrier to the inclusion of PA in NCD prevention strategies is the lack of research on PA level, which may reduce political support and policy development for PA. Thus, the aim of this study was to investigate the PA level among adults living in Sahrawi refugee camps and socioeconomic factors associated with PA. Methods A cross-sectional survey was carried out in 2014 in five refugee camps near Tindouf, Algeria. A total of 180 women and 175 men were included. PA was measured using the international physical activity questionnaire short form (IPAQ-SF). Results There was a large amount of variance in reported PA for both genders, ranging from 10 min of total PA per week to above 40 h. Forty-three percent of the participants had a low PA level (defined as not meeting the PA recommendations of 150 min of moderate to vigorous PA per day). The chi-square test of independence showed that males, those aged ≥ 60 years and people with higher education were more likely to be in the low PA level category. No significant relationship was found between PA level and BMI status. Most of the participants thought that engaging in PA would be wise, valuable, right and good but thought to a lesser degree that PA would be easy, comfortable and interesting. Conclusions Almost half of the participants were categorised as insufficiently physically active, however, most of the Sahrawi refugees express a positive attitude towards PA. PA is a low-cost approach to reducing deaths and NCDs, government initiatives to increase PA levels in refugee camps are advised.